The dissociation between pathological caloric testing and a normal video head impulse test helps differentiate between Menière’s disease, vestibular migraine, and other vestibular disorders: a confirmatory study in a large cohort of 2,101 patients - Mavrodiev, Vergil; Strupp, Michael; Vinck, Anne-Sophie; van de Berg, Raymond; Lehner, Louisa (Frontiers in Neurology, 2024)
Vestibular migraine (VM) and Menière’s disease (MD) are characterized by episodes of vertigo of similar duration. It is well known that differentiation between both diseases is not always possible based only on the patient history, physical examination, and audiological testing. In addition, the quantification of the vestibular function can also be helpful since, among patients with MD, there is often a dissociation between a normal/pseudo-normal video head impulse test (vHIT) and reduced caloric testing. The goal of this confirmatory study was to determine the sensitivity, specificity, and positive and negative predictive values (PPV and NPV) of this dissociation to differentiate between MD and VM as well as between MD and other vestibular diseases. We performed a retrospective analysis of 2,101 patients. The examination group consisted of 1,100 patients; of these, 627 (57%) had MD according to the diagnostic criteria of the Bárány Society and 473 (43%) had VM. The comparison group consisted of 1,001 patients with other peripheral, central, or functional vestibular disorders. Statistical analysis revealed the following findings for the dissociation: MD vs. VM: specificity: 83.5%, sensitivity: 58.9%, PPV: 82.6%, and NPV: 60.5%, and MD vs. all other vestibular disorders (VM plus others): specificity: 83.5%, sensitivity: 58.9%, PPV: 60.3%, and NPV: 82.7%. The dissociation between a normal vHIT and a reduced caloric response is due to the high specificity and PPV suited for the differentiation between MD and VM. This part of the study confirms previous findings in a large cohort of patients. When it comes to differentiating between MD and all observed vestibular disorders, if there is no dissociation, the diagnosis of MD is unlikely.